Meditation as a Potential Approach for Sleep-Wake Disorders - Cheng, Fung Kei (Indian Journal of Integrative Medicine, 2022)
Sleep disorders are hazardous to both physical and psychological health across different population groups, resulting in increased medical expenditure and social costs. Diverse treatments are available to cope with this problem, involving complementary and alternative therapy in which meditation is a non-medication, non-intrusive, safe and economical choice. Research supports the efficacy of various types of meditation on a wide range of sleep-related diseases among disparate bodies of people such as youngsters, the elderly, military and individuals with emotional illnesses when they practise it properly and regularly. Moreover, integrating this practice with other therapeutic measures is recommended to maximise its effectiveness; for example, counselling, music therapy, physical exercise and aromatherapy. Meditation has become a remarkable method for promoting sleep health from curative, rehabilitative and preventive perspectives.